Dari Pembebasan Jiwa kepada Islamisasi Ilmu (Membaca Pemikiran Al-Attas) - Khasib Amrullah; Usmanul Khakim; Sofian Hadi; Ahmad Sidik (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2021)
This article aims to explain the characteristics of al-Attas' Islamization. Since this idea was proposed for the first time by Syed Muhammad Naquib al-Attas in 1977 at the World Conference of Muslims in Mecca, it has prompted Muslim scholars’s interesting to make proposals about how Islamization will be aplicated. For example, Ismail Raji al-Faruqi with the institution he leads IIIT, or Maurice Bucaille's approach model which is generally called ayatization. On the many proposals, it is important to explain the characteristics of al-Attas’ Islamization as the originator of this idea. This discussion will be carried out using a content analysis, such a method interpreting al-Attas' works on Islamization.in additional a comparative analysis (comparative method). The results of this study are: First, according to al-Attas, Islamization occurs in the soul. Second, there are two stages of the Islamization they are:  (1) liberation from the traditional and secular worldview (2) incorporating key concepts of Islam. Third, If the Islamization occurs in the soul, and the soul is the location of knowledge seats, then, the Islamization is automatically leading to the Islamization of contemporary knowledge.